Upaya Kepolisian Dalam Mencegah Adanya Tindak Pidana Penyalahgunaan Senjata Tajam (Studi Pada Polres Tegal) - Zahda Ilma, Saeful Anam; Rochmani, Rochmani (Universitas Ekasakti, 2023)
The Indonesian National Police has limitations, both in terms of the availability of personnel, equipment and operational budgets. Reflecting on the duties and roles of the state in protecting all its citizens, then in the terminology of state governance anywhere in the world, namely providing civil services, providing public services and providing strengthening of community empowerment (empowering). The research used in this research is normative juridical research because it uses legal research that places law as a building system of norms. This type of normative research concerns the implementation of normative legal provisions (laws) in their actions in every particular legal event that occurs in a society. The problems that often occur in people's lives are natural laws as forms of social beings. change has hit understanding, appreciation and experience of as well as beliefs and compliance norms that exist in society itself. change has also hit the understanding of values and customs, patterns of behavior that have long lived and developed in society. Counseling is one of the efforts of the police to prevent the crime of misuse of sharp weapons among the community, namely by holding counseling about the impacts and dangers that caused by the misuse of sharp weapons. Raids are one of the police's efforts to overcome the problem of sharp weapons abuse.